2017
DOI: 10.2967/jnumed.117.189993
|View full text |Cite
|
Sign up to set email alerts
|

Brachytherapy with Intratumoral Injections of Radiometal-Labeled Polymers That Thermoresponsively Self-Aggregate in Tumor Tissues

Abstract: Brachytherapy is a type of radiotherapy wherein titanium capsules containing therapeutic radioisotopes are implanted within tumor tissues, enabling high-dose radioirradiation to tumor tissues around the seeds. Although marked therapeutic effects have been demonstrated, brachytherapy needs a complicated implantation technique under general anesthesia and the seeds could migrate to other organs. The aim of this study was to establish a novel brachytherapy using biocompatible, injectable thermoresponsive polymers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 22 publications
0
22
0
Order By: Relevance
“…Furthermore, a Lu-177-labeled peptide-based radiopharmaceutical (Lu-177-dotatate) targeting somatostatin receptor 2, which is highly expressed in neuroendocrine tumors, was approved by the Food and Drug Administration [ 31 ]. POZ–DOTA could also be labeled with these therapeutic radiometals as previously reported [ 23 ]; therefore, the application of this strategy using a radiolabeled thermoresponsive POZ would be expected for efficient internal radiotherapy of tumors.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Furthermore, a Lu-177-labeled peptide-based radiopharmaceutical (Lu-177-dotatate) targeting somatostatin receptor 2, which is highly expressed in neuroendocrine tumors, was approved by the Food and Drug Administration [ 31 ]. POZ–DOTA could also be labeled with these therapeutic radiometals as previously reported [ 23 ]; therefore, the application of this strategy using a radiolabeled thermoresponsive POZ would be expected for efficient internal radiotherapy of tumors.…”
Section: Discussionmentioning
confidence: 96%
“…A POZ derivative was synthesized as described in our previous report [ 23 ]. Its molecular structure in this study is shown in Figure 2 .…”
Section: Methodsmentioning
confidence: 99%
“…[ 2–4 ] Polymers and polymeric gels can be used as injectable biodegradable depots for controlled release of therapeutic payload or long‐term retention of drugs or therapeutic radiation sources (brachytherapy). [ 5–8 ]…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] Polymers and polymeric gels can be used as injectable biodegradable depots for controlled release of therapeutic payload or long-term retention of drugs or therapeutic radiation sources (brachytherapy). [5][6][7][8] Theranostic applications of engineered macromolecules can be greatly enhanced by bio-orthogonal click chemistry, since it enables side specific labeling or drug release inside the body. Modification with click-reactive chemical tags gives macromolecules the capability to capture, retain or release small-molecular payload, which can be a radioactive or fluorescent label for diagnostic imaging, a therapeutic radionuclide or a drug.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore this therapeutic strategy using 90 Y-labeled POZ derivatives may be promising for brachytherapy, a typical radiotherapy using "seeds" containing therapeutic radioisotopes. 89) We also developed an injectable 15 O oxygen obtained after 15 O-O 2 gas circulation into artificial lung and estimated changes in oxygen metabolism after occluding the middle cerebral artery in hypertensive rats using it. Consequently, we found that hypertension intensifies metabolic disturbances after the onset of strokes.…”
Section: Tc or 186/188mentioning
confidence: 99%